Characterization of HPV Vaccination Uptake by Birth Cohorts in a Healthcare System in Pennsylvania: A Post-COVID-19 Pandemic Historical Cohort Assessment - Josheili Y. Llavona-Ortiz DrPH, MS; Benjamin Fogel MD, MPH; Lauren J. Van Scoy MD; Casey N. Pinto PhD, MPH, CRNP; Wen-Jan Tuan DHA, MS, MPH; Sandeep Pradhan MBBS, MPH; William A. Calo PhD, JD (Cancer Control)
Background COVID-19 pandemic-related disruptions in primary care caused delays in in-person well visits for patients that were age-eligible to receive recommended preventive healthcare services. Vaccine schedules impacted by disruptions led to delays in administration of human papillomavirus (HPV), tetanus, diphtheria, and acellular pertussis (Tdap), and quadrivalent meningococcal (MenACWY) vaccines, but some studies report inconsistent findings. Our study sought to characterize changes in HPV vaccination patterns during the COVID-19 pandemic by birth cohorts in South Central Pennsylvania, compared to changes in Tdap and MenACWY vaccination. Methods Our methodological approach consisted of survival analysis techniques, such as Kaplan-Meier survival curves and Cox proportional hazards models. Patient data were analyzed by separate birth cohorts and groups of birth cohorts, with a primary interest on younger birth cohorts during the COVID-19 pandemic. Results Demographic and vaccination data from 29 928 patients born between January 1, 2000 and December 31, 2014 were analyzed. Overall, 80.1% had been vaccinated against Tdap, 81.8% against meningitis, and 67.1% against HPV by the age of 17. The adjusted hazard ratio (aHR) for HPV vaccine initiation by age 12 was the highest for patients born between 2009 and 2010 (aHR = 2.52; 95% CI: 2.34, 2.70), when compared to patients born between 2000 and 2002. However, this observation was also accompanied by a slowed increase in uptake from 63.5% (birth cohort 2006-2008) to 65.2% (birth cohort 2009-2010). Conclusion Understanding changes in vaccination uptake by birth cohorts informs the efforts of researchers and primary care practitioners to identify best practices tailored to the vaccination gaps for each group.